Evaluation of Antibacterial Activity Test For Active Extract Of Red Palm Fruit (Cyrtostachys renda Blume) against Staphylococcus aureus and Escherichia coli - Apriyanti, Sofia Elisa; Ritonga, Junia Aura Putri; Sitohang, Triyunita; Miranda, Viola Ayudya; Syamsurizal; Pratiwi, Puspa Dwi; Pratiwi, Maimum; Utami, Diah Tri; Utami, Elisma (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2025)
The two bacterial species most commonly associated with human illnesses are Staphylococcus aureus and Escherichia coli. The red palm (Cyrtostachys renda Blume) shows promise as a natural source of antibacterial agents due to its high concentration of metabolite compounds, which include phenolics, flavonoids, saponins, tannins, and terpenoids. Antibacterial activity was evaluated using the pitting diffusion method at concentrations of 92%, 46%, and 23%. The results indicated that the ethyl acetate extract exhibited the strongest antibacterial activity, with an inhibition zone measuring 26.93 mm against Eschericia coli and 20.50 mm against Staphylococcus aureus at the highest dose. Additionally, the aqueous extract demonstrated significant inhibition, while the n-hexane and dichloromethane extracts showed no antibacterial activity. The validity of the method was confirmed by using chloramphenicol as the positive control and 10% DMSO as the negative control. These findings suggest that red palm fruit has potential as a natural antibacterial agent derived from local Indonesian plants.